Potensi Ekstrak Daun Rhizophora mucronata Sebagai Antibakteri Pada Staphylococcus aureus - Edward Debari Bintar Karundeng; Evi Hanizar; Dwi Nur Rikhma Sari (Program Studi Biologi, Fakultas Sains dan Teknologi, UNIPAR JEMBER, 2022)
The purpose of the study was to determine the antibacterial properties of mangrove leaves on Staphylococcus aureus, and to determine the optimal antibacterial concentration of mangrove leaf extract. This research is an experimental type of research using the Diffusion and Dilution test to determine the MIC and MBC extracts. The sample is pure culture of S. aureus. The concentrations of mangrove leaf extracts were 0, 25, 50, 75 and 100 (%). The results of the data obtained were analyzed statistically using the Kruskal-Wallis statistical test. The results of this study showed a significant difference (95%) for the diameter of the clear zone of paper disk on the growth of S. aureus with a concentration of 0% (0.00 mm); 25% (11.04 mm); 50% (11.56 mm); 75% (12.95 mm); 100% (13.94 mm), where the higher the power the resulting resistor will widen. For MIC and KBM in the study using mangrove leaf extract, there were treatments with concentrations of 50, 75 and 100 (%).